1D/3D Co(II)-based coordination polymers: protective effect on alzheimer's disease by inhibiting neurons apoptosis and Aβ accumulation. Issue 5 (7th August 2020) - Zhang, Gui-Hong
Abstract: By using a mixed-ligand method, two new Co(II)-based coordination polymers with the chemical formula of [Co(L)(2, 2′-bipy)]n (1, 2, 2′-bipy = 4, 4′-bipyridine) and [Co(L)(phen)]n (2, phen = 1, 10-phenanthroline) have been successfully synthesized by the solvothermal reaction of 1, 4-bis(3-carboxylbenzyl)piperazine acid (H2 L) and different N-donor co-ligands with the metal salt Co(NO3 )·6H2 O. Furthermore, a grinding method was used to prepare the nanoparticles of the two coordination polymers with average size distribution around 350 and 200 nm. The protective activity against the Alzheimer's disease (AD) was assessed and the specific mechanism was discussed at the same time. First of all, the ELISA detection assay was conducted and the content of the Amyloid (Aβ) in the brain was determined after compounds 1 and 2 treatment. In addition to this, the Annexin V-FITC/PI staining was performed and the protective activity of compounds 1 and 2 on neurons was evaluated.